Identification of groundwater pollution sources in a landfill site using artificial sweeteners, multivariate analysis and transport modeling. (15th July 2019) - Stefania, Gennaro A.; Rotiroti, Marco; Buerge, Ignaz J.; Zanotti, Chiara; Nava, Veronica; Leoni, Barbara; Fumagalli, Letizia; Bonomi, Tullia
Highlights: Pollution sources for groundwater in a landfill site were assessed. A multi-methods approach integrating different techniques was used. This allows to overcome gaps and limitations of each single technique. Artificial sweeteners were integrated in the approach to trace leachate pollution. Two different main sources of pollution were identified in the studied landfill. Abstract: In this study, sources of groundwater pollution in a landfill site were identified, using artificial sweeteners as chemical tracers, multivariate statistical analysis and a quantitative analysis of the groundwater flow system through particle tracking and transport modeling. The study area, located in northern Italy, hosts an older unlined landfill and a newer lined municipal solid waste landfill placed downstream of the former. Groundwater, surface water, treated wastewater, and leachate samples were collected in March 2017 for analysis of the artificial sweeteners saccharin, cyclamate, acesulfame and sucralose together with major cations and anions, inorganic nitrogen compounds, total phosphorus, COD and some further parameters. The interpretation of the results suggests that two main leachate leaks/spills are affecting the study area. The first one concerns leachate probably spilling out of the leachate collection system serving the younger lined landfill, the other one involves leachate from the older unlined landfill that also seems to affect an area downstream of the lined landfill. Direct leachate leaks from the lined landfill seem unlikely, although they cannot be definitively excluded. This work underlines the importance of a multi-methods approach, which integrates here chemical tracers, multivariate analysis and transport modeling, for assessing groundwater pollution sources generated from complex landfill sites, where multiple and different sources may exist. In particular, this work highlights how artificial sweeteners can be used for tracing leachate plumes from landfills. The methodology applied in this study can have a broad applicability also in other polluted landfill sites worldwide.